Potential hazards and road-source apportionment of toxic trace metals in the dust from residential buildings in typical coal-utilization cities - Liu, Yuan; Zhao, Chunjie; Yang, Tianyi; Fu, Biao; Wu, Yuke; Zhang, Jiamei; Wei, Yong; Lu, Xiaoxiao (Journal of cleaner production, 2023)
Toxic trace metals in dust from residential buildings are closely related to human health, but the transmission route and impact degree of dust from coal utilization sources are still unclear. A total of 158 dust samples from different floors of 31 residential buildings in a typical coal-utilization city were collected and analyzed. Scanning Electron Microscopy (SEM) and X-ray Photoelectron Spectroscopy (XPS) were used to analyze chemical speciation and sources of trace elements. Extremely high concentrations of Zn (14,308 mg/kg), Cu (553 mg/kg), Cr (319 mg/kg), Pb (1208 mg/kg), As (30.8 mg/kg), and Cd (4.18 mg/kg) were found in the dust of residential building. Different trace elements tend to be enriched in different floor zones. The concentration of Zn was enriched in the low floor zone, while Cu and Pb were enriched in the middle floor zone, and Cd was enriched in the upper floor zone. The distribution of trace elements was found to be highly correlated between road dust and ground residential building dust, indicating that the input from road dust was the primary factor. Principal component analysis (PCA) combined with particle morphology and mineralogy study demonstrated that coal combustion, road and coal mining dust, and tire wear particles were likely sources of trace elements in dust. Risk assessments showed that As, Pb, and Cr in some samples were found to be harmful to children, particularly in high toxic forms of As (III) and PbO. This study provides systematic evidence for the transmission route and risk assessment of toxic trace metals in dust from residential building in coal-utilization cities.